Evangelization and Causes of Religion Conversion from Hindu to Christian at Badung District Bali - Ni Kadek Surpi (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
This research focuses on the effort of evangelization and religious conversion factors from Hinduism to Christianity in Badung, Bali. Bali as a unique island and famous all over the world has long been used as a target of missionary. In the early stages, the process of spreading Christianity is very slow. Even, Dutch East Indies government closed the door to evangelization and prohibited its activities in Bali. This study uses a cross field of knowledge and find that there are many causes behind the religion conversion in the area of study. Findings of this research shows that the reason for religious conversion is the social upheavals because of dissatisfaction on system and religion, individual crises, eco- nomic and socio-cultural factors, the influence of mysticism, spiritual thirst and the promise of salvation, family breakdown and urbanization, wedding and birth order in the family, education and professional evangelistic activity and lack understand- ing of Hinduism.